Ninjurin1 positively regulates osteoclast development by enhancing the survival of prefusion osteoclasts - Sung-Jin Bae; Min Wook Shin; Taekwon Son; Hye Shin Lee; Ji Soo Chae; Sejin Jeon; Goo Taeg Oh; Kyu-Won Kim (Experimental and Molecular Medicine)
Abstract Osteoclasts (OCs) are bone-resorbing cells that originate from hematopoietic stem cells and develop through the fusion of mononuclear myeloid precursors. Dysregulation of OC development causes bone disorders such as osteopetrosis, osteoporosis, and rheumatoid arthritis. Although the molecular mechanisms underlying osteoclastogenesis have been well established, the means by which OCs maintain their survival during OC development remain unknown. We found that Ninjurin1 (Ninj1) expression is dynamically regulated during osteoclastogenesis and that Ninj1−/− mice exhibit increased trabecular bone volume owing to impaired OC development. Ninj1 deficiency did not alter OC differentiation, transmigration, fusion, or actin ring formation but increased Caspase-9-dependent intrinsic apoptosis in prefusion OCs (preOCs). Overexpression of Ninj1 enhanced the survival of mouse macrophage/preOC RAW264.7 cells in osteoclastogenic culture, suggesting that Ninj1 is important for the survival of preOCs. Finally, analysis of publicly available microarray data sets revealed a potent correlation between high NINJ1 expression and destructive bone disorders in humans. Our data indicate that Ninj1 plays an important role in bone homeostasis by enhancing the survival of preOCs.